UV radiation and organic matter composition shape bacterial functional diversity in sediments - Hunting, Ellard R. (Frontiers in Microbiology, 2013)
Abstract UV radiation and organic matter (OM) composition are known to influence the species composition of bacterioplankton communities. Potential effects of UV radiation on bacterial communities residing in sediments remain completely unexplored to date. However, it has been demonstrated that UV radiation can reach the bottom of shallow waters and wetlands and alter the OM composition of the sediment, suggesting that UV radiation may be more important for sediment bacteria than previously anticipated. It is hypothesized here that exposure of shallow OMcontaining sediments to UV radiation induces OMsource dependant shifts in the functional composition of sediment bacterial communities. This study therefore investigated the combined influence of both UV radiation and OM composition on bacterial functional diversity in laboratory sediments. Two different organic matter sources, labile and recalcitrant organic matter (OM), were used and metabolic diversity was measured with Biolog GN. Radiation exerted strong negative effects on the metabolic diversity in the treatments containing recalcitrant OM, more than in treatments containing labile OM. The functional composition of the bacterial community also differed significantly between the treatments. Our findings demonstrate that a combined effect of UV radiation and OM composition shapes the functional composition of microbial communities developing in sediments, hinting that UV radiation may act as an important sorting mechanism for bacterial communities and driver for bacterial functioning in shallow lakes and wetlands.